2015
DOI: 10.1159/000368326
|View full text |Cite
|
Sign up to set email alerts
|

Primary Closure and Rate of Bile Leak following Laparoscopic Common Bile Duct Exploration via Choledochotomy

Abstract: Background: Choledocholithiasis is traditionally managed by endoscopic retrograde cholangiopancreatography or T-tube insertion following common bile duct exploration. This study examined the efficacy and safety of primary duct closure following laparoscopic common bile duct exploration (LCBDE) via choledochotomy. Methods: Between September 2011 and September 2013, 157 consecutive patients underwent LCBDE via choledochotomy. Results: Of 157 LCBDE procedures, 138 (87.9%) were successfully completed with primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
33
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 28 publications
6
33
2
Order By: Relevance
“…The data form LC, LCBDE and LCTBDE also revealed the importance of surgeon’s experience for decreasing the complication rate [24, 26, 43]. Another factor affecting the incidence of bile leakage was the diameter of CBD, which was in accordance with Hua’s study [40]. In patients with slender CBD, bile leakage occurred more frequently (<1 vs ≥1 cm, 31.6% vs 7.0%, p =  0.04).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The data form LC, LCBDE and LCTBDE also revealed the importance of surgeon’s experience for decreasing the complication rate [24, 26, 43]. Another factor affecting the incidence of bile leakage was the diameter of CBD, which was in accordance with Hua’s study [40]. In patients with slender CBD, bile leakage occurred more frequently (<1 vs ≥1 cm, 31.6% vs 7.0%, p =  0.04).…”
Section: Discussionsupporting
confidence: 57%
“…The incidence of bile leakage after primary closure following LCBDE varied dramatically [3840]. It might be attributed to the different definition of bile leakage after biliary surgery among centers.…”
Section: Discussionmentioning
confidence: 99%
“…The authors are concerned, however, that there might be selection bias, with larger stones tending to be approached via the CBD. More recent trends towards primary closure without a T‐tube are often limited by the diameter of the bile duct as a risk factor for the leak. The leak, however, is usually of little clinical importance compared with the added morbidity associated with T‐tube or stent insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Although laparoscopic CBD exploration with primary closure has had extensive global use during the past few decades, it is still trapped in controversy. [6][7][8][9] In 2002, Decker et al 10 conducted a prospective study on primary duct closure in 100 patients. They reported that the incidence of post-operative complications was 11%.…”
Section: Discussionmentioning
confidence: 99%